2015
DOI: 10.1142/s0218810415720089
|View full text |Cite
|
Sign up to set email alerts
|

Interfascicular Neurolysis for Incomplete Spontaneous Posterior Interosseous Nerve Palsy with a Surgical Delay of 17 Years: Is It Still Effective?

Abstract: A 55-year-old woman with incomplete spontaneous posterior interosseous nerve (PIN) palsy underwent interfascicular neurolysis and tendon transfer, 17 years after its onset. After one year, her nerve function partially recovered electrophysiologically. This case suggests that incomplete spontaneous PIN palsy may recover by interfascicular neurolysis, even with a long preoperative delay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The authors advocated intervening with tendon transfers if there has been no improvement in 7 months in patients aged > 50 years and within 12 months in patients aged < 50 years. More recently, the same author has reported a patient doing well with neurolysis performed 17 years after onset of symptoms (Ochi et al., 2015). There are other reports of patients improving after marked delays to treatment (Werner et al., 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The authors advocated intervening with tendon transfers if there has been no improvement in 7 months in patients aged > 50 years and within 12 months in patients aged < 50 years. More recently, the same author has reported a patient doing well with neurolysis performed 17 years after onset of symptoms (Ochi et al., 2015). There are other reports of patients improving after marked delays to treatment (Werner et al., 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Ochi et al . reported a patient doing well with neurolysis performed 17 years after the onset of symptoms ( 9 ) , and Werner et al . reported patients improving after marked delays to treatment ( 10 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, tendon transfer is recommended if there has been no improvement in 7 months in patients aged >50 years and within 12 months in patients aged <50 years (8) . Ochi et al reported a patient doing well with neurolysis performed 17 years after the onset of symptoms (9) , and Werner et al reported patients improving after marked delays to treatment (10) . Thus, PIN may recover nerve function even with a long surgical delay.…”
Section: Introductionmentioning
confidence: 99%
“…Needle electromyography showed spontaneous fibrillation potentials and positive sharp waves in the extensor carpi ulnaris and no electrical activity in the other muscles innervated by the PIN. Considering that incomplete spontaneous PIN palsy may partially recover by simple interfascicular neurolysis even 17 years after the onset (Ochi et al., 2015), interfascicular neurolysis was performed. No pathological feature, such as compression of the nerve, entrapment, fascicular constriction or hourglass-like deformity, was seen (Figure 1).…”
mentioning
confidence: 99%